BAT3 regulates Mycobacterium tuberculosis protein ESAT-6-mediated apoptosis of macrophages. - Ajay Grover; Angelo A Izzo (PLoS ONE)
HLA-B-associated transcript 3 (BAT3), also known as Scythe or BAG6, is a nuclear protein implicated in the control of apoptosis and natural killer (NK) cell-dendritic cell (DC) interaction. We demonstrate that BAT3 modulates the immune response by regulating the function of macrophages. BAT3 is released by macrophages in vitro and it down-regulates nitric oxide and proinflammatory cytokines release in IFN-γ and LPS stimulated macrophages. Furthermore, Mycobacterium tuberculosis-derived protein ESAT-6 (Rv3875) induced transient increase in the expression and release of BAT3 in macrophages. We show that induction of apoptosis by ESAT-6 is dependent on the cleavage of BAT3 by caspase-3 and proteasomal degradation. Our results also indicate that BAT3 regulates ESAT-6-induced apoptosis by interacting with anti-apoptotic protein BCL-2. Taken together, the data suggest that BAT3 plays a role in the early immune response to M. tuberculosis infection and may be a key protein associated with the fate of antigen presenting cells during infection.